Scholarly Adventures in Digital Humanities - Battershill, Claire. author. aut Link
XV, 182 p. 5 illus.
Keywords: “This genre-bending, delightful book is about so much more than might at first appear: the revolution of digital humanities; feminist collaborative scholarship; pedagogy; adventures in the archives; modernism; book history; publishing . . . It is hard to imagine anyone working in the humanities today who could not benefit from reading about the scholarly adventures and discoveries behind the Modernist Archives Publishing Project.” — Mark Hussey, Distinguished Professor of English at Pace University, USA This book addresses the gap between print and digital scholarly approaches by combining both praxis and theory in a case study of a new international collaborative digital project, the Modernist Archives Publishing Project (MAPP). MAPP is an international collaborative digital project, funded by the Social Sciences and Humanities Research Council of Canada, that uses digital tools to showcase archival traces of twentieth-century publishing. The twenty-first century has witnessed, and is living through, some of the most dynamic changes ever experienced in the publishing industry, arguably altering our very understanding of what it means to read a book. This book brings to both general readers and scholarly researchers a new way of accessing, and thereby assessing, the historical meanings of change within the twentieth-century publication industry by building a resource which organises, interacts with, and uses historical information about book culture to narrate the continuities and discontinuities in reading and publishing over the last century. Claire Battershill is Banting Postdoctoral Fellow in the Department of English at Simon Fraser University in Vancouver, Canada. Helen Southworth is Associate Professor of Literature in the Robert D. Clark Honors College at the University of Oregon, USA. Alice Staveley is Lecturer and Director of Honors in the Department of English, Stanford University,USA. Michael Widner is Academic Technology Specialist in the Division of Literatures, Cultures, and Languages at Stanford University, USA. Elizabeth Willson Gordon is Assistant Professor of English at The King’s University in Edmonton, Canada. Nicola Wilson is Lecturer in Book and Publishing Studies at the University of Reading, UK.